Social and Legal Healthcare Models and Their Functioning During a Global Crisis - Mokhov, Alexandre Anatolievich; Svirin, Yury Alexandrovich; Gureev, Vladimir Aleksandrovich; Kulakov, Vladimir Viktorovich; Shestov, Sergej Nikolaevich (Cuestiones Políticas, 2020)
The article analyzes the existing health models in terms of their legal, economic and social effectiveness, innovative potential, as well as in the context of their ability to resist modern threats caused by changes in the environment, ecology, bio-information development and other technologies. The authors used the methods of comparative analysis, synthesis, structural-functional and statistical analysis. Everything indicates the need for a major modernization of existing care models and / or their replacement by new ones that satisfy the basic needs of the majority of society at the current stage of its development. Among the most prominent findings, it is also highlighted that the health insurance model is a creation of the late 19th and early 20th centuries. It was developed and implemented at a time when the economy, society, the social sphere, and technologies were completely different. The 2020 pandemic has revealed the reasons for the unsatisfactory health care work, in a seemingly as prosperous country as the United States, where the largest amount of budget money traditionally goes to health care.